ANALISIS MITIGASI BENCANA SEBAGAI UPAYA MANAJEMEN RISIKO BENCANA TANAH LONGSOR - Zulfa, Vira Ananda; Widyasamratri, Hasti (Pondasi, 2023)
Landslide disasters are the 3rd highest disaster intensity in Indonesia that happened in 2020. Â The impact of landslide disasters causes damage to the community such as deaths, missing and injured people, and property losses to private and public facilities. Landslide disaster management can be done through landslide disaster mitigation planning as an effort to minimize the impact of landslides. Landslide mitigation can be based on the urgency or needs of the region based on the level of risk of landslide disasters. The method in this paper uses mitigation case studies based on the level of landslide risk from several regions. The results of this paper showed various programs of landslide disaster mitigation in both structural and non-structural ways . Those programs are based on the urgency according to the classification of landslide risk levels. The results in this paper are also expected to be considered in disaster mitigation planning both structurally and non-structurally appropriate to the needs of the region.